An ECG changed the life of a young boy: a case of arrhythmogenic right ventricular dysplasia. (24th October 2014) - Altun, Ibrahim; Akin, Fatih; Sahin, Cem; Beydilli, Halil
Abstract : Arrhythmogenic right ventricular dysplasia (ARVD) is a progressive condition with the right ventricular myocardium being replaced by fibrofatty tissue. It is a hereditary disorder mostly caused by desmosome gene mutations. The prevalence of arrhythmogenic right ventricular cardiomyopathy is about 1/1000–5000. Clinical presentation is usually related to ventricular tachycardias, syncope, presyncope or ventricular fibrillation leading to cardiac arrest, mostly in young people and athletes. We report a case of a 17-year-old boy from Turkey, who was referred to our cardiology department for an ECG, required of him prior to joining a football team.